2008
DOI: 10.2111/07-109.1
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Long-Term Vegetation Change Related to Grazing Systems, Precipitation, and Mesquite Cover

Abstract: Rangeland scientists struggle with how long rangeland experiments must continue in order to detect treatment effects, particularly in semiarid ecosystems characterized by slow responses and high spatiotemporal variability. We compared changes in eight grass and three shrub categories to grazing systems (yearlong vs. seasonal rotation with equivalent long-term stocking rates), and covariates (precipitation and mesquite [Prosopis velutina] gradients) over 12 yr (1972-1984) and 34 yr (1972-2006) on the Santa Rita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…This finding is consistent with studies from drier climates (Fuhlendorf and Smeins, 1997;Fuhlendorf et al, 2001;Yao et al, 2006;Mashiri et al, 2008;Butterfield et al, 2010;Moran et al, 2014). Plot, grazing and precipitation had the largest coefficients, but the consistency with which past effects appear highlights their importance.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is consistent with studies from drier climates (Fuhlendorf and Smeins, 1997;Fuhlendorf et al, 2001;Yao et al, 2006;Mashiri et al, 2008;Butterfield et al, 2010;Moran et al, 2014). Plot, grazing and precipitation had the largest coefficients, but the consistency with which past effects appear highlights their importance.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the use of plots as the experimental unit instead of grazing management unit presents a case of pseudo-replication (Hurlbert, 1984). Access to permanent plots in a greater number of grazing units, as in other studies (Mashiri et al, 2008), would have been preferred but was unavailable. Given the large allotment sizes (2000e22,000 ha) and dispersion of our plots we feel enough heterogeneity in soil type, elevation (2308e2810 m) and precipitation (325e485 mm year À1 ) was captured to interpret our results despite probable statistical dependence in both time and space of the plots.…”
Section: Grassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Year-round grazing was practiced from 1916-1972, with stocking rates steadily decreasing from a maximum of 0.17 animal unit years per hectare in 1918 (Browning et al 2008). A rotational grazing system was implemented in 1972 and maintained through the time of our study (see Mashiri et al 2008).…”
Section: Study Sitementioning
confidence: 99%
“…The absence of significant differences in green grass cover between UG and G1, and standing dead cover between UG and G2 indicates that despite the importance of grazing intensity in determine the magnitude of grazing impacts, the length of grazing treatment may also contribute to the outcome of interaction between herbivore and vegetation. Masbiri et al [60] indicated that two criteria must be met for grazing effects to be detected: the effects must be larger than the variability in the system and they must reach this size during the period of observation. Compared to G3, the length of grazing treatment in the G1 and G2 sites are relatively short.…”
mentioning
confidence: 99%